Seasonality effects on Dengue - Rodrigues, Helena Sofia (2014)
Dengue is a vector-borne disease transmitted from an infected human to an Aedes mosquito, during a blood-meal. A model for dengue disease transmission is presented, composed by human and mosquitoes compartments. The aim of this work is to simulate the effects of seasonality, on the vectorial capacity. Using entomological information about the mosquito behavior under different temperatures, simulations were carried out and the repercussions on the disease transmission were analyzed.